Antioxidant activity of Ardisia Crispa (Mata pelanduk) - Hassan Mahmood Kzar Jindal,; Jamaludin Mohamad, (Universiti Kebangsaan Malaysia, 2012)
The leaf and fruit crude extracts of hexane, chloroform, methanol and water of Ardisia crispa were screened for their antioxidant activity using DPPH radical scavenging, ferric reducing power, and metal chelating antioxidant assay. The methanol crude extract of fruits showed higher antioxidant activity (90.16 ± 0.01%) than the methanol crude extract of leaves (82.24 ± 0.02%) in the DPPH radical scavenging assay. In the ferric reducing power assay methanol fruit extract showed the highest absorbance indicating high antioxidant activities than leaf extract. In the metal chelating antioxidant assay fruit methanol extract gave 40% antioxidant activities than the leaf. Thin Layer Chromatography of the fruit methanol crude extract showed that it contained phenolic compounds when it was detected with folin reagent. HPLC analysis revealed that the fruit methanol extract contained gallic acid. This indicated that the high antioxidant activities of the fruits were due to the presence of gallic acid in the fruits of Ardisia crispa.